2017
DOI: 10.1515/ethemes-2017-0022
|View full text |Cite
|
Sign up to set email alerts
|

The Analysis of Agricultural Products Export Competitiveness of the Republic of Serbia Based on the RCA Index

Abstract: Agriculture of the Republic of Serbia is a significant economic branch, due to the specifics of production, tradition and because of the enormous potential that it holds for improving competitive performance and development of the national economy. For this reason, in all strategic documents agriculture is recognised as a vital branch for the development of the national economy, which can be achieved by an increase in productivity and greater foreign exchange, especially with the neighbouring countries. Bearin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…The test statistic for the RCA model indicated that the LOGPM, the LOGGDPC and crises are negatively related to the RCA, whereas the LOGLABOUR and the LOGCAPFORM variables had a positive relationship with the RCA. This showed that increase in the price of agricultural products will lead to drop in demand as the price of agricultural products is expensive, and this in turn results in loss of competitiveness in the agriculture export (Tuah, 2013;Aziz, 2013;Cvetković & Petrović-Ranđelović, 2017). Besides, Othman et al (2009) indicated that highly priced agricultural products will impede the competitiveness and its value-added products in the export market.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The test statistic for the RCA model indicated that the LOGPM, the LOGGDPC and crises are negatively related to the RCA, whereas the LOGLABOUR and the LOGCAPFORM variables had a positive relationship with the RCA. This showed that increase in the price of agricultural products will lead to drop in demand as the price of agricultural products is expensive, and this in turn results in loss of competitiveness in the agriculture export (Tuah, 2013;Aziz, 2013;Cvetković & Petrović-Ranđelović, 2017). Besides, Othman et al (2009) indicated that highly priced agricultural products will impede the competitiveness and its value-added products in the export market.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, growth in the commodities' price consequently led to a loss of competitiveness in the tradable sector that triggered exchange rates to appreciate due to the movement of resources to a growing sector. This can be supported by the discovery of Cvetković and Petrović-Ranđelović (2017) who stated that low price of agricultural products is one of the major aspects of export competitiveness. Bhattacharya (2011) stated that income is expected to linked positively with competitiveness in which the import volume will expand as GDP increases.…”
Section: Agriculture Background In Malaysiamentioning
confidence: 94%
“…When looking at RCA1 indicator, there is no signifi cant difference between Croatia and Romania only (2-3). With RCA2 indicator, the difference is not signifi cant between Serbia and Croatia (1-2), or Bulgaria and Bosnia & Herzegovina (4)(5). According to MI indicator, there is no signifi cant difference between Serbia and Bulgaria (1)(2)(3)(4), or between Croatia and Roma- (3)(4)(5).…”
Section: Rezultati I Raspravamentioning
confidence: 99%
“…RCA2 measures the comparative advantage of industry or product export and its competitive ability. It is calculated by using the formula: (4) .......Cvetanović, Nikolić, Cvetanović: Wood Industry Trade Competitiveness of Selected... For RCA2 variables, the following applies: when RCA2 = -1, export does not exist and then e sc = 0; -1 < RCA2 < 0 points to comparative disadvantages; when RCA2 = 0, export is equal to import, i.e. then e sc = i sc ; 0 < RCA2 < 1 indicates the existence of comparative advantage; and when RCA2 = 1, this means that import does not exist, i.e.…”
Section: Indicators Of Industry and Sector Trade Competitiveness 22mentioning
confidence: 99%
“…Apart from the national level, competitiveness can also be observed at the level of individual export segments where the Revealed Comparative Advantages (RCA) index is often used (Fidan, 2009;Kumar & Singh, 2015;Mizik et al, 2020). The use of this index mainly refers to the export of the agri-food sector and its parts (Cvetković & Petrović-Ranđelović, 2017). Also, the RCA index is used mainly for international comparisons and external competitiveness testing.…”
Section: Literature Reviewmentioning
confidence: 99%